Monitorare per conservare: il caso della Torre Ghirlandina di Modena - Coïsson, Eva; Ferrari, Lia; Zanazzi, Elena (Restauro Archeologico, 2023)
The monumental complex consisting of the cathedral, tower and main square of Modena (Northern Italy) has been a UNESCO World Heritage Site since 1997. The visible tilting of the Ghirlandina tower has always generated concerns for its preservation, even more after the recent seismic events. This paper highlights the role of structural monitoring for the conservation of the site, with particular reference to the data acquired during the recent Emilia earthquakes. Unexpectedly, the inclination of this leaning tower decreased after the major seismic event. Some considerations are presented regarding the difficulty of modelling this kind of effects on buildings with complex historical stratifications and the application of the observational method, derived from geotechnical engineering, is proposed. The importance of structural monitoring is once again recalled, in order to preserve world heritage and comply with the principle of minimum intervention.